Supporting Learning Engagement with Online Students - Janet R Buelow; Thomas A. Barry; Leigh E Rich (Online Learning, 2019)
University students are increasingly demanding that traditionally taught courses are converted to an online platform. While quality standards are in place for the format and organization of online courses, professors often are left wondering what activities contribute to learning engagement for their online students. The research question driving this study was, what activities contribute to learning engagement for online students? To investigate this question, an online survey was conducted in one state university of all students taking an online course during the spring semester. With responses from 417 students and using three standardized scale variables for learning engagement, as well as two open-ended questions, course components related to strong learning engagement were identified and examined. Initial findings indicated a statistically significant moderate correlation of learning engagement with the use of higher-order learning and reflective and integrative learning techniques. Specifically, students who reported being highly engaged connected ideas from other courses, changed their understanding of a topic or concept, found connections between their learning and societal problems, and had fun. A regression model using these variables, along with control variables of student age, gender, and out-of-school work, resulted in an R2 of 0.484, suggesting that almost half of the variance in learning engagement can be explained via this model. Further analysis of the qualitative data identified certain aspects of online discussions and assignments as engaging, such as discussions and interactive assignments that are not merely “fun” from a student perspective but also integrate previous learning and connect to current social issues. This includes prompting students with thought-provoking questions that relate to “real-world” situations and inviting students to share diverse opinions as well as develop personal perspectives.